Comfort of walking in the city center of Kuala Lumpur - Zakaria, Juriah; Ujang, Norsidah (Elsevier, 2015)
A walkable place allows people to experience the city on foot pleasantly. The environmental qualities which facilitate walking determine a pedestrian's sense of comfort. This paper focuses on walkability of urban places in the city center of Kuala Lumpur. The objective of this study is to determine pedestrians’ satisfaction of comfort based on their walking experience. The findings indicated that most of the respondents were fairly satisfied with the level of comfort particularly in terms of pedestrian facilities provided. In contrast, field observation revealed that the city center had poor maintenance of facilities reflected in improper condition of walkways and street furniture.